PENGARUH PERSEPSI KARIR, PERTIMBANGAN PASAR KERJA, DAN PENGHARGAAN FINANSIAL TERHADAP MINAT BERKARIR DI BIDANG PERPAJAKAN (Studi Kasus Pada Mahasiswa Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa) - Andri Waskita Aji; Sri Ayem; Yuli Rizky Cendykia Tegar Ratrisna (Fakultas Ekonomi UNIBBA, 2022)
This study aims to determine the effect of career perceptions, labor market considerations, and financial rewards on interest in a career in taxation. This type of research is an associative research type and data collection uses primary data using a questionnaire via google form. In this study, samples were taken, namely students of the accounting study program, Faculty of Economics, Universitas Sarjanawiyata Tamansiswa. The sampling technique used the snowball sampling technique. The number of processed data is 100 respondents. This study uses data analysis, namely multiple regression analysis which is processed using the SPSS version 20 program. The results show that career perception has a positive effect on career interest in taxation, labor market considerations have a positive effect on career interest in taxation, and financial rewards have a positive effect on interest in a career. a career in taxation